2007
DOI: 10.1128/mcb.01282-06
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Prevents UVB-Induced Cyclooxygenase 2 Expression: Coupled mRNA Stabilization and Translational Inhibition

Abstract: Cyclooxygenase 2 (COX-2) is a key enzyme in the conversion of arachidonic acid to prostaglandins, and COX-2 overexpression plays an important role in carcinogenesis. Exposure to UVB strongly increased COX-2 protein expression in mouse 308 keratinocytes, and this induction was inhibited by apigenin, a nonmutagenic bioflavonoid that has been shown to prevent mouse skin carcinogenesis induced by both chemical carcinogens and UV exposure. Our previous study suggested that one pathway by which apigenin inhibits UV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 59 publications
10
79
2
2
Order By: Relevance
“…Our data confirm previous findings that mRNA stabilizing, and thus posttranscriptional COX-2 regulatory mechanisms do operate in RAW264.7 macrophages (16). At present, a multiplicity of mRNA-stabilizing and -destabilizing factors such as TIAR, AUF1, HuR, and TIA-1 are known (15) and implicated in COX-2 regulation (16,17,35). Previous work also suggested a role of HuR in COX-2 mRNA stabilization after treatment of human mammary epithelial cells with taxanes (13).…”
Section: Discussionsupporting
confidence: 80%
“…Our data confirm previous findings that mRNA stabilizing, and thus posttranscriptional COX-2 regulatory mechanisms do operate in RAW264.7 macrophages (16). At present, a multiplicity of mRNA-stabilizing and -destabilizing factors such as TIAR, AUF1, HuR, and TIA-1 are known (15) and implicated in COX-2 regulation (16,17,35). Previous work also suggested a role of HuR in COX-2 mRNA stabilization after treatment of human mammary epithelial cells with taxanes (13).…”
Section: Discussionsupporting
confidence: 80%
“…Our group and others have shown that apigenin treatment of cells results in a wide variety of antitumorigenic and chemopreventive actions (13)(14)(15)(16)(17)(18). More recently, we have focused our investigative efforts on determining the effects of apigenin treatment on keratinocytes exposed to UVB radiation (19,20), the primary causative agent of skin cancers.…”
Section: Introductionmentioning
confidence: 99%
“…At the translational level, apigenin increased the localization to cytoplasm of two proteins, HuR and T-cell-restricted intracellular antigen 1-related protein (TIAR). HuR and TIAR then bound to the AU-rich elements in the 3'-untranslated region of COX2 mRNA and inhibited COX2 translation (Tong et al, 2007). In addition to its inhibitory effects on COX2 expression, apigenin acts as a natural antagonist of the TBX A2 receptors.…”
Section: Apigeninmentioning
confidence: 99%